2014
DOI: 10.1111/grs.12057
|View full text |Cite
|
Sign up to set email alerts
|

Screening of biomass production of cultivated forage grasses in response to mycorrhizal symbiosis under nutritional deficit conditions

Abstract: Arbuscular mycorrhizal fungi (AMF) colonize the root systems of most natural grassland species and usually increase plant growth by enhancing nutrients provision. This effect on growth responses of cultivated forage grasses is scarcely known, particularly under nutritional deficit conditions. We examined total biomass production, aboveground and belowground biomass and tillering of three temperate and three tropical cultivated forage grasses. Seedlings of each species were inoculated with a mixture of mycorrhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…The number of tillers could not be correlated to the mycorrhizal colonization of P. millegrana in all the treatments. Likewise, Cavagnaro et al (2014) confirmed that the number of tillers in P. dilatatum was not influenced by the use of AMF isolates, despite the higher tiller biomass than that of the control The mycorrhizal colonization of P. millegrana in the control, native, native + UFLA05 and native + UFLA401 treatments did not correlated to the biomass parameters (dry mass, root length and root volume). However, in the mixture treatment, a positive correlation between mycorrhizal colonization and dry shoot matter (r = 0.90, 0.1 ≤ p <0.05) and root length (r = 0.93, 0, 1 ≤ p <0.05) could be observed.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…The number of tillers could not be correlated to the mycorrhizal colonization of P. millegrana in all the treatments. Likewise, Cavagnaro et al (2014) confirmed that the number of tillers in P. dilatatum was not influenced by the use of AMF isolates, despite the higher tiller biomass than that of the control The mycorrhizal colonization of P. millegrana in the control, native, native + UFLA05 and native + UFLA401 treatments did not correlated to the biomass parameters (dry mass, root length and root volume). However, in the mixture treatment, a positive correlation between mycorrhizal colonization and dry shoot matter (r = 0.90, 0.1 ≤ p <0.05) and root length (r = 0.93, 0, 1 ≤ p <0.05) could be observed.…”
Section: Resultsmentioning
confidence: 54%
“…The increase of the root volume of P. millegrana with native + UFLA351 and native + UFLA372 is linked to the intense formation of fine roots, which increase the surface area for water and nutrient absorption, as observed for other species of Paspalum (CHANNABASAVA; LAKSHMAN;MUTHUKUMAR, 2015;CAVAGNARO et al, 2014).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Despite the importance of B. brizantha pastures for fodder livestock, our knowledge of the AMF species diversity associated with this species is limited. These kinds of studies are essential since some researchers suggest that the presence of AMF can increase the plant species yield (Cavagnaro, Oyarzabal, Oesterheld, & Grimoldi, ), the soil maintenance and an equilibrated environment (Baum et al., ; Paterson et al., ; Pollastri et al., ). The study aimed to contribute to the knowledge of the AMF species richness in B. brizantha pastures in Oaxaca lowlands (Gulf of Mexico), Mexico and explore its relationship with soil properties.…”
Section: Introductionmentioning
confidence: 99%